Selected Aspects of Nitrogen Refinement of Silumin 226 - Szymczak, Tomasz; Gumienny, Grzegorz; Pacyniak, Tadeusz (My University, 2014)
The work presents the results of the investigations of the effect of the nitrogen (N2) refining time „τraf” and the gas output on the course of the crystallization process, the microstructure and the gassing degree of silumin 226 used for pressure casting. The refinement of the examined silumin was performed with the use of a device with a rotating head. The crystallization process was examined by way of thermal analysis and derivative analysis TDA. The performed examinations showed that the prolongation of the N2 refining time causes a significant rise of the temperature of the crystallization end of the silumin, „tL”, as well as a decrease of its gassing degree, „Z”. An increase of the nitrogen output initially causes an increase of the temperature „tL” and a drop of the gassing degree „Z”, which reach their maximal values with the output of 20 dm3/min. Further increase of the output causes a decrease of the value „tL” and an increase of „Z”. The examined technological factors of the refining process did not cause any significant changes in the microstructure of silumin 226.
Keywords: Theoretical basics of casting processes; Pressure casting; Refining; TDA method; procesy odlewnicze; odlewanie ciśnieniowe; silumin; rafinacja; metoda TDA